2015
DOI: 10.1093/mnras/stv2569
|View full text |Cite
|
Sign up to set email alerts
|

Empirical microlensing event rates predicted by a phenomenological model

Abstract: Estimating the number of microlensing events observed in different parts of the Galactic bulge is a crucial point in planning microlensing experiments.Reliable estimates are especially important if observing resources are scarce, as is the case for space missions: K2, WFIRST, and Euclid. Here we show that the number of detected events can be reliably estimated based on statistics of stars observed in targeted fields. The statistics can be estimated relatively easily, which makes presented method suitable for p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 12 publications
5
64
1
Order By: Relevance
“…First overtone models exhibit much faster (a factor of a few up to 10) higherṖ than fundamental mode models. This is consistent with first overtone pulsators exhibiting faster and more erratic period changes than fundamental mode Cepheids (Poleski 2008). Very long-period Cepheids, i.e., those which cross the IS only once (cf.…”
Section: Rates Of Period Changesupporting
confidence: 83%
See 1 more Smart Citation
“…First overtone models exhibit much faster (a factor of a few up to 10) higherṖ than fundamental mode models. This is consistent with first overtone pulsators exhibiting faster and more erratic period changes than fundamental mode Cepheids (Poleski 2008). Very long-period Cepheids, i.e., those which cross the IS only once (cf.…”
Section: Rates Of Period Changesupporting
confidence: 83%
“…For the SMC, we use 213 Cepheids with positive and 285 Cepheids with negativeṖ as listed in Pietrukowicz (2002). Poleski (2008) cautions thatṖ values derived from insufficiently long temporal baselines are not necessarily suitable for comparisons with stellar evolution models, since suchṖ values can be dominated by short-term fluctuations rather than secular evolution (see also Berdnikov et al 2000Berdnikov et al , 2009. Studies ofṖ over longer temporal baselines would be very useful for more accurate tests of stellar models.…”
Section: Rates Of Period Changementioning
confidence: 99%
“…These stars typically have more sinusoidal-like light curves, for instance, Polaris and FF Aql (Neilson et al 2012a;Turner et al 2013a,b). Because of the shape of the light curve, determining the time of light minimum is more difficult than for a fundamental-mode Cepheid (Poleski 2008). A typical sinusoidal light curve is shown in Fig.…”
Section: Results For First-overtone Pulsationmentioning
confidence: 99%
“…It has become evident that large positive-P dot objects are relatively more common among long-P orb systems than expected. Poleski et al (2011) reported a large negative (−2 × 10 −3 ) period variation of superhumps in OGLE-BLG-DN-001, an SU UMa-type dwarf nova in the period gap. Their data, however, covered the growing stage of superhumps and this large negative P dot is most likely a result of stage A-B transition.…”
Section: Period Derivatives During Stage Bmentioning
confidence: 97%